Pilot protection method based on K-L divergence for offshore wind power low-frequency cable feeder line - Shuping Gao; Yongning Zhou; Chenqing Wang; Jinyu Zhou; Zhihui Zhao; Guobing Song (International Journal of Electrical Power & Energy Systems)
Low-frequency AC cable feeder is an important part of low-frequency transmission systems. Due to the influence of the double-side converter control strategy, its fault characteristics are obviously different from those of the conventional power grid, which makes it difficult for differential protection to meet the reliability requirements. To solve the above problems, according to the fault current difference between the two sides of the low-frequency transmission line, a low-frequency cable outgoing line protection method based on Kullback-Leibler divergence is proposed in this paper. Firstly, the fault currents at both ends of the cable line are extracted. Then the probability distribution of the extracted current on both sides are calculated. Thirdly the K-L divergence value is calculated and the protection criteria are given. According to the difference of K-L divergence value between internal and external fault occurrence, internal and external fault can be identified. Finally, the offshore wind power low-frequency transmission system model is built in PSCAD/EMTDC to output fault data, which is processed by Matlab to verify the protection method. The simulation results show that the method has good sensitivity and reliability in offshore wind power low-frequency cable feeder transmission lines, which is less affected by the transition resistance. It can not only withstand up to 300 Ω transition resistance, but also has strong resistance to noise interference and data anomalies and is capable of identifying all kinds of faults quickly and reliably.